Analysis of reactive astrogliosis in mouse brain using in situ hybridization combined with immunohistochemistry - Muraleedharan, Ranjithmenon (STAR Protoc, 2021)
Reactive astrogliosis is characterized by a profound change in astrocyte phenotype in response to all CNS injuries. Here, we present a revised in situ hybridization and immunohistochemistry (IHC) protocol to label the reactive astrocytes in the mouse brain. Several approaches for quantifying astrocyte reactivity lacked sensitivity to discriminate across the spectrum. We optimized in situ hybridization followed by IHC. We provide a staining protocol for quantitative measures of astrocyte reactivity as an independent confirmation of the magnitude of reactive gliosis. For complete details on the use and execution of this protocol, please refer to Muraleedharan et al. (2020).